Fangirl down : [large type] a novel - Bailey, Tessa (Harper Large Print, an imprint of HarperCollinsPublishers, 2024)
"Once golf's fastest rising star, Wells Whitaker's career craters before his eyes, despite the ongoing support of a beautiful redhead who always cheers him on from the sidelines, who he eventually invites to be his new caddy"--